Listening, Hearing, Sensing: Three Modes of Being and the Phenomenology of Charles Sanders Peirce. Issue 2 (8th April 2014) - Bodie, Graham D.; Crick, Nathan
Abstract: This article accepts Lipari's invitation to continue rethinking communication along the lines of artful listening as understood through the lens of phenomenology. However, we trace out the implications following a different phenomenological tradition than the one stemming from the German tradition of Heidegger and Husserl—specifically, the phenomenology of Charles Sanders Peirce, who allows us to see listening differently and perhaps more clearly. The primary contribution from Peirce's phenomenology is the logos he uses to extract 3 fundamental categories of thought and nature: Firstness (Quality), Secondness (Relation), and Thirdness (Mediation). As we shall show, listening is characterized by a plural consciousness sensitive to Mediation as it reveals itself through Relation and Quality.